Crystal Channel Engineering for Rapid Ion Transport: From Nature to Batteries. Issue 11 (23rd December 2021) - Mei, Jun; Liao, Ting; Sun, Ziqi
Abstract: Ion transport behaviours through cell membranes are commonly identified in biological systems, which are crucial for sustaining life for organisms. Similarly, ion transport is significant for electrochemical ion storage in rechargeable batteries, which has attracted much attention in recent years. Rapid ion transport can be well achieved by crystal channels engineering, such as creating pores or tailoring interlayer spacing down to the nanometre or even sub‐nanometre scale. Furthermore, some functional channels, such as ion selective channels and stimulus‐responsive channels, are developed for smart ion storage applications. In this review, the typical ion transport phenomena in the biological systems, including ion channels and pumps, are first introduced, and then ion transport mechanisms in solid and liquid crystals are comprehensively reviewed, particularly for the widely studied porous inorganic/organic hybrid crystals and ultrathin inorganic materials. Subsequently, recent progress on the ion transport properties in electrodes and electrolytes is reviewed for rechargeable batteries. Finally, current challenges in the ion transport behaviours in rechargeable batteries are analysed and some potential research approaches, such as bioinspired ultrafast ion transport structures and membranes, are proposed for future studies. It is expected that this review can give a comprehensive understanding on the ion transport mechanisms within crystals and provide some novel design concepts on promoting electrochemical ion storage capability in rechargeable batteries. Abstract : Inspired by rapid and selective ion transport behaviours commonly identified in biological systems, ion transport properties in solid and liquid crystals are crucial for electrochemical ion storage in rechargeable batteries, including electrode materials and electrolytes, which are critically reviewed and summarized. It is expected that this review could provide some new design principles for high‐performance rechargeable batteries based on this understanding of natural ion transport phenomena.